L'herméneutique du sujet : cours au Collège de France, 1981-1982 - Foucault, Michel 1926-1984; Ewald, François; Fontana, Alessandro 1939-2013; Gros, Frédéric; Collège de France (Paris Gallimard Seuil, 2001)
In the course he devoted in 1982 to 'L'herméneutique du sujet', Michel Foucault presented an investigation into the notion of 'Self-Consciousness', which, much more than the famous 'Know thyself', organises the practices of philosophy. The aim is to show the techniques, procedures and historical purposes by which an ethical subject is constituted, in a determined relationship to the self.These studies go beyond the strict framework of the history of philosophy. By describing the ancient mode of subjectivation, Michel Foucault seeks to make clear the precariousness of the modern mode of subjectivation. By re-reading the Ancients, he allows us to question our identity as modern subjects. All his work consists in making us more alienated from ourselves, by showing the historicity of what could seem the most anhistorical: the way in which, as subjects, we relate to ourselves.What this passage to the Ancients also allowed was a reformulation of the political problem: what if the struggles today were not only struggles against political dominations, not only struggles against economic exploitations, but struggles against identity-based subjugations? Michel Foucault, rereading Plato and Marcus Aurelius, Epicurus and Seneca, is looking not for something to overcome, but for something to rethink politics.
Includes bibliographical references and indexes.
Keywords: Philosophy; Education